THE FORMATION OF INFRASTRUCTURE ONSIDERATION OF THE VIEWS OF PUBLIC TRANSPORT PASSENGERS: FOREIGN AND DOMESTIC EXPERIENCE - D. Plotnikova (Вестник университета)
The article presents the foreign and domestic experience of organizations in the field of public transport, based on the consideration of the views of passengers. The data on International Association of public transport, the Berlin Union of passengers, as well as the first domestic Association «The passengers’ union» are given. The author believes that for more effective work of all types of public transport constant coordination of work of state bodies, companies and public organizations, reflecting the interests of all categories of passengers is required.